Predictive possibility of the transverse cerebellar diameter to abdominal circumference ratio for small-for-gestational-age fetus suspected as a cause of maternal placental syndromes: a retrospective cohort study - Satoshi Shinohara; Yasuhiko Okuda; Shuji Hirata; Kohta Suzuki (Hypertension in Pregnancy, 2020)
Objective To examine whether fetal transverse cerebellar diameter (TCD) to abdominal circumference (AC) ratio can predict small-for-gestational age suspected as a cause of maternal placental syndromes (SGA-MPS). Methods We evaluated 473 women who underwent ultrasound examinations at 24–28 weeks of gestation. A receiver operating characteristic curve was used to determine the TCD/AC ratio thresholds to predict SGA-MPS. We used multivariable logistic regression analysis to examine the association. Results TCD/AC ratio>14.37 was associated with SGA-MPS. Conclusions Accurate risk stratification using the TCD/AC ratio could assist in managing patients with small-for-gestational-age fetuses at risk of developing MPS-associated adverse outcomes.